Karen's pen pal - Martin, Ann M.; Tang, Susan; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1992)
Karen thinks having a pen pal in New York City is very cool. But when her pal Maxie turns out to be a big bragger, Karen starts to make up stories.
"A Little Apple paperback."
Keywords: Sisters; Friendship; Stepfamilies; Pen pals; Honesty